PENGEMBANGAN KOGNITIF PADA PENDIDIKAN HOLISTIK DALAM PEMBELAJARAN AGAMA HINDU DI SD NO. 11 JIMBARAN KABUPATEN BADUNG - Ni Kadek Sinta Pratiwi (UHN I Gusti Bagus Sugriwa Denpasar, 2023)
Cognitive is one of the areas of competence in holistic education that must be developed. Cognitive development can be developed through various lessons, one of which is Hindu religious learning. Cognitive development at SD No. 11 Jimbaran in Hindu learning has actually been carried out but there are still many things that need to be improved in the learning process and the methods used by teachers so that students are interested in learning. This is the background of the research entitled